Effectiveness of warm compress in the management of complications among patients with peripheral intravenous infusion - K.PACKIALAKSHMI; T. VIDHYA (International Journal of Pharma and Bio Sciences, 2017)
When patients get admitted in the hospital for treatment; 90% of cases receive peripheral intravenous (PIV) therapy to treat various conditions. The patients are prone to get peripheral intravenous complications (PIVC). Health professionals should be vigilant of the right interventions to expedite comfort for the patients on intravenous therapy and take measures to reduce the complications. The objectives of the study were effect of warm compress in the management of PIVC, associate the management of PIVC scores with the selected demographic variables. One group pretest and posttest design was adopted in this study. 30 samples were selected with inclusive criteria by non-probability purposive sampling technique. Warm compress was applied twice a day for three days. The findings of the study presented that the calculated paired ‘t’ value of PIVC such as superficial thrombophlebitis, pain and intravenous infusion were 11.5, 13.07and 5.7, respectively, statistically significant at p<0.001 of pretest with posttest3. Hence, warm compress was effective to treat PIVC which is cheapest, feasible to adopt, to save money and material.